The Effect of Product Quality, Brand Image, and Price Perception on the Decision to Purchase Products from PT Toa Coating Indonesia - Syumi, Mey (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives : The paper examines the influence of product quality, brand image, and price perception on consumer purchasing decisions in Indonesia’s paint industry motivated by the growing competition among paint distributors and the increasing importance of brand reputation in shaping consumer preferences Background Problems : Do product quality, brand image, and price perception significantly influence purchasing decisions among consumers in Indonesia’s paint market? Novelty : The novelty of this paper lies in its integrated examination of both tangible (product quality and price) and intangible (brand image) factors within the paint industry context, an area that has received limited empirical attention in Indonesian research Research Methods : This research adopts a quantitative approach using survey data collected from 102 respondents who have purchased paint products from various end users. The data were analyzed using correlation and multiple regression tests through SPSS to assess the relationships and significance levels among variables. Finding/Results : There is a significant relationship between brand image, price perception, and purchasing decisions of consumers. This finding indicates that a positive brand image and a well-perceived price can strongly influence consumers’ willingness to make a purchase. Conclusion: The findings of this research provide valuable insights for companies aiming to increase their sales performance and market competitiveness. Businesses can use these results to strengthen their marketing strategies by focusing on building a consistent brand image and adjusting price perceptions to meet consumer expectations.